2020
DOI: 10.1002/mnfr.201900982
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Anti‐Inflammatory Mechanism/Triggers of d‐Allulose: A Profile Study of Microbiome Composition and mRNA Expression in Diet‐Induced Obese Mice

Abstract: Scope The results of recent studies on d‐allulose intervention in high‐fat diet (HFD)‐fed mice suggest that d‐allulose has a substantial impact on obesity. In addition, several studies have uncovered bacterial candidates among the gut microbiota associated with obesity and inflammation in mice. To identify the d‐allulose‐attenuated genes related to the inflammation‐associated bacterial candidates, two types of statistical analyses are performed. Methods and results Using liver and epididymal fat tissues, genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Allulose significantly decreased the mRNA expression levels of TLRs, NF-kappa B, PI3K-AKT, cytokines, and chemokines ( Figure 4A,B), in addition to plasma inflammatory cytokine levels ( Figure 4C). Consistent with these results, our previous study showed that mRNA expression associated with inflammation significantly decreased in the ALL group compared with that in the HFD group, in both hepatic and adipose tissue [43].…”
Section: Discussionsupporting
confidence: 84%
“…Allulose significantly decreased the mRNA expression levels of TLRs, NF-kappa B, PI3K-AKT, cytokines, and chemokines ( Figure 4A,B), in addition to plasma inflammatory cytokine levels ( Figure 4C). Consistent with these results, our previous study showed that mRNA expression associated with inflammation significantly decreased in the ALL group compared with that in the HFD group, in both hepatic and adipose tissue [43].…”
Section: Discussionsupporting
confidence: 84%
“…AL supplement tended to decrease plasma resistin levels compared to controls [ 43 ]. d -allulose in a high-fat diet reduced diet-induced obesity and markedly decreased plasma inflammatory cytokine levels and related mRNA expression [ 44 ]. These findings show that AL supplementation can reduce inflammatory responses that may contribute to reduced weight gain and T2DM in db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with D-fructose and D-glucose, D-allulose has a much stronger antioxidative activity that persists over a long period of storage [ 43 , 44 , 45 , 46 ], and is highly soluble [ 47 ]. D-allulose showed hypoglycemic properties and therapeutic effects on type 2 diabetes [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. It also has antiobesity [ 54 , 55 , 58 , 59 ] and antihyperlipidemic effects [ 42 , 60 ].…”
Section: Rare Sugars In Food Systems and Medicinementioning
confidence: 99%